Effect of Micropolar Fluid Flow on Unsteady Convective Diffusive Mass Transfer in Doubly Connected Region - Ramarao, Indira; Jagadeesha, S.; Rashmi, K. R.; Sreegowrav, K. R. (Communications in Mathematics and Applications, 2023)
Solute transfer in a micropolar fluid flowing between two concentric cylindrical tubes is considered. The governing equations are solved analytically for velocity. The species transport equation is solved by using a long-time approach following Sankara Subramanian and Gill model to obtain mean concentration and coefficients of dispersion. The results are analysed with respect to a catheterized artery for the parameter values available in the literature. The effects of micro-rotation, reaction rate, and inner tube radius on the diffusive, convective, and dispersion coefficients are analysed by graphically depicting the numerical results.